A SEMIOTICS ANALYSIS IN MUSIC VIDEOS OF EARTH BY LIL DICKY AND LIFE GOES ON BY BTS (PANOPTICON: Journal of English Studies, 2022)
The purposes of this study are to find out the sign and the description of denotation, connotation, and myth meaning in the music video of Earth by Lil Dicky and Life Goes On by BTS. In analyzing both music videos, the writer used qualitative method and applied Barthes’ theory. The sign shows that the signs are denotation and connotation meaning. While, the denotation reflected in the music video Lil Dicky’s Earth music video is about life on the Earth, while in BTS’ Life Goes On music video is about life that must o on in a pandemic. The connotation reflected in the Lil Dicky’s Earth music video is about the life problems that we face the world, and BTS’ Life Goes On music video is about support to all people and the world which is not well. Lastly, the myth reflected in both of the music videos are about problems on Earth symbolized with the structure of circumstances and climate change.Keywords: Connotation, Denotation, Music Video, Semiotics